Efeito da terapia por fotobiomodulação associada a material de carbono impregnado com nanopartículas de prata no controle do crescimento bacteriano e na viabilidade de osteoblastos - Rodrigues, Ayres Fernando (2023)
Osteomyelitis is an inflammatory process of infectious origin in the bone tissue, which affects the lives of patients in the physical, emotional, social and economic aspects. Photobiomodulation therapy (PBM) is a non-invasive treatment modality, used in osteo-articular diseases, with an anti-inflammatory, analgesic and modulating effect on cell activity. The carbon material has favorable characteristics for use as a biomaterial, while silver is known for its antimicrobial effect. Objective: To evaluate the effect of PBM on carbon material impregnated with silver nanoparticles in controlling the growth of Staphylococcus aureus (S aureus) and maintaining the viability of osteoblasts. Methodology: The adsorption and desorption capacity of the carbon material in nanosilver solution (81ppm) was evaluated. Then, the material impregnated with nanosilver was used for the microbiological and cellular study. In the microbiological study, S aureus were cultivated in carbon material impregnated with silver and irradiated with blue LED (400nm; 106J/cm2; 353mW/cm2) and bacterial growth was evaluated in agar or in BHI medium solution. In the cellular study, Osteoblasts were cultured on carbon material impregnated with nanosilver and irradiated with blue LED in the same previous parameters. Results: The carbon material impregnated with silver nanoparticles reduced the growth of S aureus when irradiated with blue LED. Osteoblasts maintained cell viability when cultured in medium with carbon material impregnated with nanosilver. The carbon material showed an important adsorption action in the nanosilver solution. Conclusion: Carbon material impregnated with silver nanoparticles and irradiated with blue LED (400nm; 106J/cm2; 353mW/cm2) controls the growth of S aureus without altering the viability of osteoblasts.